Host defence during Klebsiella pneumonia relies on haematopoietic-expressed Toll-like receptors 4 and 2 - Wieland, C W; van Lieshout, M H P; Hoogendijk, A J; van der Poll, T (The European respiratory journal, 2011)
In this study, the relative roles of Toll-like receptor (TLR)2 and TLR4 were investigated independently and together. Moreover, we studied the role of haematopoietic compartment in anti-Klebsiella host defence. We infected TLR2 and TLR4 single-, and TLR2×4 double knockout (KO) animals with different doses of Klebsiella pneumoniae. In addition, bone marrow chimeric mice were created and infected. TLR4 played a more prominent role in antibacterial defence than TLR2, considering that only TLR4 KO mice demonstrated enhanced bacterial growth in lungs and spleen 24 h after infection with 3×10³ colony-forming units of Klebsiella compared with wild-type (WT) mice. In late-stage infection or after exposure to a higher infectious dose, bacterial counts in lungs of TLR2 KO animals were elevated compared with WT mice and TLR2×4 KO animals were more susceptible to infection than TLR4 KO mice. TLR signalling in cells of haematopoietic origin is of primary importance in host defence against K. pneumoniae. These data suggest that: 1) TLR4 drives the antibacterial host response after induction of pneumonia with relatively low Klebsiella doses; 2) TLR2 becomes involved at a later phase of the infection and/or upon exposure to higher bacterial burdens; and 3) haematopoietic TLR2 and TLR4 are important for an adequate host response during Klebsiella pneumonia.